FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - HILLARY SUMILAT; NICKEN DESTRIANA (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this study is to examine the factors that influence corporate social responsibility disclosure in non financial companies. These factors are managerial ownership, public ownership, foreign ownership, board independence, audit committees, firm size, firm age, leverage, profitability, and liquidity. Population of this research are non financial companies listed in Indonesia Stock Exchange from 2012-2015. The samples of this study are 152 data using purposive sampling method. This research uses multiple regression method to test the hypothesis. The result of this study shows that foreign ownership and firm size have influence to corporate social responsibility disclosure but managerial ownership, public ownership, board independence, audit committees, firm age, leverage, profitability, and liquidity do not have influence to corporate social responsibility disclosure.